2017
DOI: 10.5603/cj.a2016.0091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cyclosporine A use in the prevention of reperfusion injury in acute myocardial infarction: A meta-analysis

Abstract: Background: Reperfusion injury is an important limiting factor associated with revascularization in acute myocardial infarction (AMI (OR 1.05,. Similarly, we did not find any significant differences in terms of cardiogenic shock, recurrent ischemia and myocardial infarction, heart failure and echocardiographic outcomes. Conclusions: Cyclosporine A is not helpful in preventing reperfusion injury in AMI. (Cardiol J 2017; 24, 1: 43-50)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In the past decade, several in vitro and in vivo studies have confirmed the involvement of MPT in ischemia/RI [83]. The administration of CsA (as well as its analog FK506) has been shown to protect against ischemia/RI in multiple animal models and in multiple tissues, including cardiac and skeletal muscle, brain, kidney, liver, lungs, and testis [84][85][86][87][88][89]. Ppif -KO mice are significantly protected from ischemia/RI in both cardiac muscle and the brain, in terms of both tissue function and survival rates [31,32,90].…”
Section: Role Of Mpt In Reperfusion Injurymentioning
confidence: 98%
“…In the past decade, several in vitro and in vivo studies have confirmed the involvement of MPT in ischemia/RI [83]. The administration of CsA (as well as its analog FK506) has been shown to protect against ischemia/RI in multiple animal models and in multiple tissues, including cardiac and skeletal muscle, brain, kidney, liver, lungs, and testis [84][85][86][87][88][89]. Ppif -KO mice are significantly protected from ischemia/RI in both cardiac muscle and the brain, in terms of both tissue function and survival rates [31,32,90].…”
Section: Role Of Mpt In Reperfusion Injurymentioning
confidence: 98%
“…Cyclosporine A, a known MPTP desensitiser, has been shown to induce appreciable protection in acute myocardial infarction [33]. However, a recent meta-analysis failed to show any benefit of cyclosporine A post-infarction [34]. Other forms of preconditioning have also been suggested in an attempt to inhibit MPTP formation have shown some promise in animal studies [3537].…”
Section: Primary Graft Dysfunctionmentioning
confidence: 99%
“…Side branch occlusion, atherosclerotic debris embolization and ischemia/reperfusion injury are the main reasons for PCIrelated myocardial injury. Various adjunctive pharmacological agents and methods have been tried to reduce ischemia reperfusion injury but none of them have been proven (14)(15)(16) . Remote ischemic preconditioning is an easy, cheap, and practical method.…”
Section: Discussionmentioning
confidence: 99%